2012
DOI: 10.1177/0272989x12443416
|View full text |Cite
|
Sign up to set email alerts
|

Choosing between Hospitals

Abstract: Consumers consider patient experience-based information at least as important as hospital-based information. They rely most on information regarding physicians' expertise, waiting time, and physicians' communication when choosing a hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…In an Internet study of factors involved in choosing between hospitals, investigators showed that the experience of other patients was considered at least as important in making a choice as information provided by the hospitals [21]. The patient-attributed “report card grade regarding physicians expertise” had the highest relative importance in making a choice.…”
Section: Discussionmentioning
confidence: 99%
“…In an Internet study of factors involved in choosing between hospitals, investigators showed that the experience of other patients was considered at least as important in making a choice as information provided by the hospitals [21]. The patient-attributed “report card grade regarding physicians expertise” had the highest relative importance in making a choice.…”
Section: Discussionmentioning
confidence: 99%
“…While patients have long used the experiences of friends and family in choosing hospitals, service users can now more systematically access collected information on patient experience (eg, Consumer Assessment of Health care Providers and Systems reports in the United States [ 8 ] and NHS Choices in the United Kingdom [ 9 ]). There is evidence that information based on patient experience is considered at least as important by service users choosing between different providers as different performance indicators provided by hospitals or reporting bodies [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive approach to DCE is an established method in evaluating healthcare choices, [33][34][35][36] and comparisons between adaptive and more standard DCE approaches show comparable results, [37][38][39] with the adaptive approach allowing screening of a larger number of attributes and levels with a lower number of subjects. ADCE also limits some bias.…”
Section: Discussionmentioning
confidence: 99%